Clinical and public policy interventions to address food insecurity among children. Issue 1 (February 2022) - Brochier, Annelise; Garg, Arvin; Peltz, Alon
Abstract : Purpose of review: This article describes the impacts of food insecurity (FI) on child health, outlines clinical and public policy interventions to mitigate FI in children, and defines new paradigms in population health to ameliorate the harmful effects of FI in children. Recent findings: Rates of FI among children have dramatically increased with the onset of the COVID-19 pandemic, with particular adverse impact on low-income children. Population health innovations in screening, referral, and social service integration offer new opportunities to address FI. Summary: Despite advances in clinical practice and public policy, FI remains a persistent issue for many US children. Clinicians and policymakers have opportunities to leverage clinical and community-based integration to improve service delivery opportunities to ameliorate childhood hunger and racial and socioeconomic inequity in the United States.